2018
DOI: 10.36233/0372-9311-2018-1-3-9
|View full text |Cite
|
Sign up to set email alerts
|

Functional Groups of Bifidoflora of Intestinal Microbiota in Associative Symbiosis of Human

Abstract: Aim. Aim of the research is the identification of functional groups of human gut bifidoflora based on analysis of the spectrum of metabolites features, proteome, bioprofile, immunoregulatory properties and the ability to differentiate «self/non-self» among the associative microbiota. Materials and methods. The materials are 260 strains ofbifidobacteria isolated from 122 intestinal microsymbiocenoses. Experimental studies were carried out using bacteriological, chromatographic and immunological methods. Statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…Bifidobacterium longum is a common member of the human gut microbiota and is frequently present at high numbers in the human gut microbiota throughout life, which is indicative of a close symbiotic host-microbe relationship (1, 2). The B.…”
Section: Announcementmentioning
confidence: 99%
“…Bifidobacterium longum is a common member of the human gut microbiota and is frequently present at high numbers in the human gut microbiota throughout life, which is indicative of a close symbiotic host-microbe relationship (1, 2). The B.…”
Section: Announcementmentioning
confidence: 99%
“…Bifidobacteria are important representatives of the obligate microflora of the human intestine and occupy the leading position among representatives of the indigenous microflora, forming the basis of colonization resistance of the host due to the production of antimicrobial substances and stimulation of the factors of innate and adaptive host immunity against pathogens ( 1 , 2 ). The genus Bifidobacterium is a member of the Actinobacteria phylum and Bifidobacteriaceae family ( 3 ).…”
Section: Announcementmentioning
confidence: 99%
“…It has been shown that they are one of the few reliable human mutualists that do not have pathogenic properties, regardless of the state of the host organism [ 9 ]. Factual materials have been accumulated, indicating that some types of bifidobacteria have stably settled in the large intestine and remain our faithful helpers, participating in the maintenance of homeostasis [ 10 ]. Note that the relatively small number of bifidobacteria in adults and the relatively small size of the genome do not reflect their functional role in microsymbiocenosis.…”
mentioning
confidence: 99%
“…The specific and quantitative paucity of representatives of this taxonomic branch, established by the results of microbiome studies, indicates the phylogenetic remoteness/isolation from most pathogenic and opportunistic intestinal bacteria, which complicates the process of horizontal transfer of pathogenicity and antibiotic resistance genes between them [ 11 ]. No islands of pathogenicity have been identified in bifidobacteria to date, despite several cases of their fixation (together with other microorganisms) in some infectious and inflammatory diseases [ 10 ]. The number and diversity of intra- and extrachromosomal mobile genetic elements in bifidobacteria are small, and the peculiarities of their organization do little to facilitate their transfer to other microorganisms [ 12 , 13 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation